State survival bureaucracy (SSB): State sustainability after Arab revolutions - Abdulmonem Almashat; Salwa Thabet (Review of Economics and Political Science (REPS), 2019)
Purpose - Non-politicized bureaucracy plays a fundamental role in the survival of states during times of transition and drastic change. Moreover, non-politicized bureaucracy protects state institutions from failing. In fact, state survival bureaucracy (SSB), as an alternative to Deep State, obtains all mechanisms for the sustainability of the state, both its entity and identity. In case of resistance to the elected officials and executives' abrupt decisions, professionals and experts came up with Deep State to reflect the elements of rejection. Design/methodology/approach - The paper uses both system and function approaches in analyzing the role of bureaucracy in states going through transition. It also draws comparisons from the harsh experiences in the Arab region after Arab revolutions where most of the states collapsed while Tunisia and Egypt survived. The authors will use the available literature in reviewing different arguments regarding the role of bureaucracy in addition to the own observations as scholars who were engaged in the political process in Egypt for sometimes and during the drastic changes since January 25, 2011 and the knowledge about political process in Tunisia and other Arab states. Findings - In the study of the collapse of a number of Arab states and the survival of Tunisia and Egypt, it was found out that it is SSB which holds state together in cases of drastic changes or tangible threats. SSB includes bureaucrats and policy implementing agencies that are committed to both entity and identity of the state. The role of SSB emerges clearly in a state of utmost survival crisis of the state. SSB does inherently obtain self-correcting mechanisms that help states face, experience drastic change and cope with it. Originality/value - Non-politicized bureaucracy plays a fundamental role in the survival of states during times of transition and drastic change. Moreover, non-politicized bureaucracy protects state institutions from failing. In fact, SSB as an alternative to Deep State, as defined in this paper, obtains all mechanisms for the sustainability of the state, both its entity and identity. The analysis will show how SSB is a constructive mechanism for the survival of the state when its entity and identity as well as well-established national interests are under tangible threats.
Keywords: 330; Bureaucracy; Deep state; Non-politicized bureaucracy; Politicized bureaucracy; State survival bureaucracy; State sustainability